Adaptive Immune Responses and Immunity to SARS-CoV-2 - Primorac, Dragan; Vrdoljak, Kristijan; Brlek, Petar; Pavelić, Eduard; Molnar, Vilim; Matišić, Vid; Erceg Ivkošić, Ivana; Parčina, Marijo (Frontiers in Immunology, 2022)
Since the onset of the COVID-19 pandemic, the medical field has been forced to put in relation the basic knowledge of immunology with the up-to-date SARS-CoV-2 findings and translate it to the population of the whole world in record time. Following the infection with the viral antigen, adaptive immune responses are mostly activated by viral particle encounter with the antigen-presenting cells or B cell receptors which induce further biological interactions in order to defend the host against the virus. After the infection has been warded off, the immunological memory is developed. The SARS-CoV cellular immunity has been reported to persist even 17 years after the infection despite the undetectable humoral component. Similarly, in a shorter stretch of time similar has been reported for the SARS-CoV-2 T cell memory by assessing the interferon-gamma levels when heparinized blood is stimulated with the virus-specific peptides. T cells also play an irreplaceable part in a humoral immune reaction as the backbone of a cellular immune response. They both provide the signals for B cell activation as well as the maturation, competence, and memory of the humoral response. Here, we interpret recent SARS-CoV-2 available research, which encompasses the significance and current understanding of the adaptive immune activity, and compare it among native, exposed, and vaccinated blood donors. Most robust responses have been found in individuals who have acquired the ‘hybrid immunity’ – both vaccinated and previously infected. Additionally, we analyze the humoral response in immunocompromised patients and memory mediated by cellular immunity and the impact of clonality taking place in the SARS-CoV-2 pandemic with regards to breakthrough infections and variants of concern, both Delta and Omicron variants.